Short Video Affecting Young People's Intention to Travel To Sichuan as a Destination - Wang, Xinjie; Jiang, Songyu (Ann Publisher, 2025)
Background. With the proliferation of short video platforms such as Douyin, digital media has become a powerful tool for destination marketing, particularly among younger generations. Aims This study investigates the impact of short video attributes—perceived usefulness, perceived ease of use, perceived price, and emotional experience—on young people's attitude toward travel and their intention to visit Sichuan, a culturally rich and economically significant tourist destination in China. Methods. Using a quantitative approach, data were collected via an online questionnaire distributed through social media platforms. A total of 417 valid responses were obtained using stratified random sampling targeting Chinese Douyin users aged 18–35. Structural Equation Modeling (SEM) was employed to test the hypothesized relationships and mediating effects. Result. The results show that perceived ease of use, usefulness, and emotional experience significantly affect both travel attitude and intention, with travel attitude serving as a key mediator. However, perceived price was not a significant direct predictor of intention. Conclusion. These findings offer theoretical contributions to digital tourism research and practical insights for enhancing destination promotion strategies through short video platforms. Implication. Tourism authorities in Sichuan and similar destinations should consider integrating interactive short video strategies with localized cultural elements, optimize pricing information presentation, and engage users through storytelling formats that elicit positive emotions